Does climatic change in precipitation drive erosion and desertification in Naxos Island, Greece? - Nastos, P.; Evelpidou, N.; Vassilopoulos, A. (10th Plinius Conference on Mediterranean Storms (EGU), 2008)
In this paper we are examining the state of Naxos Island as far as erosion is concerned, using precipitation indexes produced from daily precipitation totals and Geographical Information System (GIS) in order to develop an erosion risk model. Naxos Island belongs to the Cycladic area and is situated at the central Aegean Sea, in Greece. The relief of the island is mountainous, with a central mountain chain crossing it from north to south. The geology of Naxos is characterised by a migmatite irruption, metamorphic rocks (schist, gneiss, marble), and sedimentary rocks (Neogenic and Quaternary deposits). Tectonism of the area is low nowadays but in the past geological time has played a major role defining the present morphology. Although the mean annual precipitation appear to be low (~360.0 mm), the erosion processes of the area are very intense, because of the intensive character of precipitation, the high slope relief, the differential lithology and the absence of important land cover. The aforementioned factors are the major contributing to the formation of the present denudated morphology mainly because of the intense run off.